PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA DOSEN MELALUI KEPEMIMPINAN PADA UNIVERSITAS LAMAPPAPOLEONRO KABUPATEN SOPPENG - Tenripada, A. Nazalia Ramadhani We; Kadir, Moh. Akob; Abdullah, Salma (LP2M Universitas Bina Bangsa, 2025)
This research was conducted with the aim of: (1) to find out the influence of Work Discipline on Lecturer Performance at Lamappapoleonro University. (2) to find out the effect of Compensation on Lecturer Performance at Lamappapoleonro University. (3) Knowing the influence of Work Discipline on Leadership at Lamappapoleonro University. (4) Knowing the influence of Compensation on Leadership at Lamappapoleonro University. (5) Knowing the influence of Leadership on Lecturer Performance at Lamappapoleonro University. (6) Knowing the influence of work discipline on Lecturer Performance through Leadership at Lamappapoleonro University. (7) Knowing the effect of Compensation on Lecturer Performance Through Leadership at Lamappapoleonro University. The analysis methods used are descriptive analysis, volatility test, reliability test, classical assumption test, multiple linear regression test, and Path analysis. The data was analyzed using the Statistical Product and Service Solution (SPSS) software program 21. The results of this study show that: (1) Work Discipline affects Lecturer Performance at Lamappapoleonro University. (2) Compensation affects the Performance of Lecturers at Lamappapoleonro University. (3) Work Discipline affects Leadership at Lamappapoleonro University. (4) Compensation affects Leadership at Lamappapoleonro University. (5) Leadership affects the performance of lecturers at Lamappapoleonro University. (6) Work discipline affects Lecturer Performance through Leadership at Lamappapoleonro University. (7) Compensation affects Lecturer Performance Through Leadership at Lamappapoleonro University